Parartemiopsis longicornis (Smirnov), senior synonym of P. mongolica Rogers (Crustacea: Branchiopoda: Anostraca), with remarks on the validity of the genus - Rogers, D. Christopher (Zootaxa, 2006)
Parartemiopsis mongolica Rogers, 2005 was described on the basis of two male specimens from Mongolia. Subsequent to publication, it was demonstrated that this taxon had previously been described as Chirocephalus longicornis (Smirnov, 1930). However, a comparison between the male genitalia of C. longicornis and those of other Chirocephalus species, as well as Artemiopsis, demonstrates that the genus Parartemiopsis Rogers, 2005 is still valid. Therefore, the correct name for this taxon is Parartemiopsis longicornis (Smirnov, 1930).